Semantics of floristic images in the poetry of Oleksandr Oles (on the material of the collection “The Grief and the Joy hugging”) (Literatures of the World: Poetics, Mentality and Spirituality, 2018)
The article investigates the specifics of using floral images in the poetic works of Oleksandr Oles, who is one of the brightest representatives of the Ukrainian literary context in the 19th and 20th centuries.This paper focuses on the material of the author's first poetic collection and the relevance of floristic images in his early poetry. It also determines the leading features of the content, functional and stylistic meaning of floral images in lyrical poetry of the poet. This research emphasizes the ambivalence of using analyzed images and their multi-functionality in the author's poetic discourse. The paper considers the correlation of the folklore tradition and the individual-authorial imagery in terms of using vegetative images in poetic texts. The main emphasis is put on the peculiarities of functioning floristic images while revealing the emotions and feelings of the lyrical character, his psychological states and processes.
Keywords: floristic image; romanticism; folklore tradition; artistic image; ambivalence